1992
DOI: 10.1073/pnas.89.6.2002
|View full text |Cite
|
Sign up to set email alerts
|

Methods and algorithms for statistical analysis of protein sequences.

Abstract: We describe several protein sequence statistics designed to evaluate distinctive attributes ofresidue content and arrangement in primary structure. Considered are global compositional biases, local clustering of different residue types (e.g., charged residues, hydrophobic residues, Ser/Thr), long runs of charged or uncharged residues, periodic patterns, counts and distribution of homooligopeptides, and unusual spacings between particular residue types. The computer program SAPS (statistical analysis of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
208
0
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(212 citation statements)
references
References 20 publications
1
208
0
2
Order By: Relevance
“…We have noted that the expressed PARG protein can form dimers stable to SDS-PAGE conditions. In that regard, residues 871-907 show significant homologies to known leucine zipper dimerization sequences (48). Another motif identified is a putative bipartite nuclear location signal (NLS) (49).…”
Section: Discussionmentioning
confidence: 99%
“…We have noted that the expressed PARG protein can form dimers stable to SDS-PAGE conditions. In that regard, residues 871-907 show significant homologies to known leucine zipper dimerization sequences (48). Another motif identified is a putative bipartite nuclear location signal (NLS) (49).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the C. albicans CTR1 protein sequence using the SAPS analysis program (http://www.isrec.isb-sib.ch/software/ SAPS_form.html; Brendel et al, 1992) revealed a predicted protein of 251 amino acids with a molecular mass of 27?8 kDa, lacking an amino-terminal leader sequence. Dancis et al (1994a) previously reported that S. cerevisiae Ctr1p has a methionine-and serine-rich amino-terminal region that contains a putative copper-binding domain.…”
Section: Resultsmentioning
confidence: 99%
“…Quantification was performed by using standard curves for each amino acid, and results recalculated to be expressed as mol%. The following indices from amino acid compositional analysis were also calculated: KR (Lys + Arg): positive charge; ED (Glu + Asp): negative charge; KR + ED: total charge; KR-ED: net charge; LVIFM (Leu + Val + Ile + Phe + Met): major hydrophobics; and the groupings AGP (Ala + Gly + Pro) (encoded by CCN, GCN, and GGN codons), and FIKMNY (Phe + Ile + Lys + Met + Asn + Tyr) (encoded by AAN, AUN, UAN, and UUN codons), according to Brendel et al (Brendel et al 1992). …”
Section: Amino Acid Analysismentioning
confidence: 99%